Pembelajaran Interaktif dan Reflektif dalam PAI: Efektivitas Model RICOSRE-FC Berbantuan Wordwall terhadap Keterampilan Berpikir Kritis Peserta Didik - Djailani, Abdul Kadir; Siti Khumairah Fiqrillah; Zulmihram; Sarmawati; Ahmad Sauki; Batriani (Rayah Al-Islam, 2025)
The critical thinking skills of class VIII students of SMP Negeri 4 Majene are still relatively low, as seen from the lack of responses to teacher questions, difficulties in understanding the material, and less conducive classroom behavior. The purpose of this study was to optimize critical thinking skills through the application of the RICOSRE-FC learning paradigm with Wordwall media. The research employed Kemmis and Taggart's spiral model of Classroom Action Research (CAR) model in two cycles, which included the stages of observation, reflection, action, and planning. A total of 19 students were involved. The data collection instrument was a critical thinking skills questionnaire analyzed using a score scale and percentage. The results showed an increase in completeness from 78.95% in the pre-action to 89.47% in cycle I, then increased again to 94.74% in cycle II. A total of two students in cycle II were categorized as very high, while the low category decreased. The most prominent indicator was Elementary Clarification, which showed students' ability to explain simply. The application of the RICOSRE-FC model assisted by Wordwall has proven effective in creating interactive and reflective learning, thereby empowering students' critical thinking skills.